2016
DOI: 10.1177/1744806916666083
|View full text |Cite
|
Sign up to set email alerts
|

A SCN10A SNP biases human pain sensitivity

Abstract: Background: Nav1.8 sodium channels, encoded by SCN10A, are preferentially expressed in nociceptive neurons and play an important role in human pain. Although rare gain-of-function variants in SCN10A have been identified in individuals with painful peripheral neuropathies, whether more common variants in SCN10A can have an effect at the channel level and at the dorsal root ganglion, neuronal level leading to a pain disorder or an altered normal pain threshold has not been determined. Results: Candidate single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 54 publications
5
60
2
Order By: Relevance
“…De novo gain-of-function mutations of Na v 1.8 that produce DRG neuron hyperexcitability have been found in 4% of a group of 393 consecutive patients diagnosed with small fiber neuropathy (SFN) at one medical center, including familial episodic pain syndrome (FEPS2, OMIM#61551), establishing a role for this channel in pathogenesis [19; 59], and a single nucleotide polymorphism biases experimental pain in healthy human subjects [46]. The gain-of-function attributes that these mutations confer on Na v 1.8 include hyperpolarized voltage-dependence of activation, accelerated recovery from inactivation, enhanced ramp current and impaired inactivation.…”
Section: Nav18 In Human Peripheral Painful Neuropathymentioning
confidence: 99%
“…De novo gain-of-function mutations of Na v 1.8 that produce DRG neuron hyperexcitability have been found in 4% of a group of 393 consecutive patients diagnosed with small fiber neuropathy (SFN) at one medical center, including familial episodic pain syndrome (FEPS2, OMIM#61551), establishing a role for this channel in pathogenesis [19; 59], and a single nucleotide polymorphism biases experimental pain in healthy human subjects [46]. The gain-of-function attributes that these mutations confer on Na v 1.8 include hyperpolarized voltage-dependence of activation, accelerated recovery from inactivation, enhanced ramp current and impaired inactivation.…”
Section: Nav18 In Human Peripheral Painful Neuropathymentioning
confidence: 99%
“…They also demonstrated an association between SCN10A rs6795970 and higher thresholds for mechanical pain in experimental pain testing. [15] However, in our study, we identified that patients with the 3312Tallele (3312G>T) and A allele (rs6795970) had a higher risk of presenting with inadequate analgesia.…”
Section: Discussionmentioning
confidence: 56%
“…They are preferentially expressed in dorsal root ganglion sensory neurons and sympathetic ganglia and significantly influence nociceptor excitability. [15,38,39] Recent genetic studies have identified rare and common mutations in SCN9A and SCN10A as contributory both in chronic pain conditions and postoperative pain. [15,16,39] Guangyou Duan et al reported that 3312G>T (SCN9A), a nonsynonymous SNP leading to the amino acid substitution V1104L in human Nav1.7, was associated with postoperative inadequate analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations